A retrospective review of the palliative surgical management of malignant pleural effusions. Issue 2 (20th June 2013) - Bell, David; Wright, Gavin
Abstract : Background: A malignant pleural effusion (MPE) can be associated with debilitating dyspnoea. Determining optimal surgical management involves balancing the quality of palliation, degree of short-term dysfunction and expected duration of patient survival. Objective: To examine differences in postoperative survival after different surgical approaches to MPEs and to analyse the relationship between primary tumour site and duration of postoperative survival. Design, setting and subjects: Data from patients who underwent implantation of a tunnelled pleural catheter, video-assisted thoracoscopic surgery (VATS) pleurodesis or decortication at a thoracic surgical service from February 2001 to October 2010 were retrospectively reviewed. Measurements and results: 291 procedures were performed in 283 patients. The three most common primary malignancies were non-small cell lung cancer (NSCLC) (n=69), breast (n=62) and mesothelioma (n=49). Median postoperative survival was 184 days for NSCLC patients, 221 days for breast cancer patients and 595 days for mesothelioma patients. Tunnelled pleural catheters were implanted in 33 patients with a median survival of 92 days. VATS pleurodeses were performed in 224 patients with a median survival of 227 days. Decortications were performed in 26 patients with a median survival of 379 days. Conclusions: Results reflect that procedures can be successfully matched to projected survival, although prognosis is not informed by primary tumour site, age or sex. Further to this, results are consistent with the policy that the procedures resulting in the shortest hospital stay and lowest peri-operative morbidity should be reserved for patients with the shortest predicted survival.